Joy ride [videorecording (DVD)] - Lim, Adele; Chevapravatdumrong, Cherry; Hsiao, Teresa, 1985-; Park, Ashley; Cola, Sherry, 1989-; Hsu, Stephanie (Actor); Wu, Sabrina; Chieng, Ronny; Hagner, Meredith, 1987-; Denman, David, 1973-; Mumolo, Annie; Simons, Timothy; et al. (Lionsgate, 2023)
The hilarious and unapologetically explicit story of identity and self-discovery centers on four unlikely friends who embark on a once-in-a-lifetime international adventure. When Audrey's business trip to Asia goes sideways, she enlists the aid of Lolo, her irreverent, childhood best friend who also happens to be a hot mess; Kat, her college friend turned Chinese soap star; and Deadeye, Lolo's eccentric cousin. Their no-holds-barred, epic experience becomes a journey of bonding, friendship, belonging, and wild debauchery that reveals the universal truth of what it means to know and love who you are.